DETERMINASI NIAT E-WALLET GENERASI Z: PERSPEKTIF INTERNAL DAN EKSTERNAL - Nisrina Luthfia Rahmasari; Zaki Baridwan (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2026)
The use of e-wallets in Indonesia continues to increase alongside government support through the National Non-Cash Movement to promote economic digitalization. However, World Bank data shows that in 2024 only around 42.7% of Indonesians aged 15 and above have used digital payments. This figure remains relatively low compared to other Southeast Asian countries such as Malaysia and Thailand. Therefore, it is necessary to analyze the factors influencing individuals’ intention to use e-wallets, represented by social influence, trust, self-efficacy, and financial literacy. This study employs a quantitative approach using questionnaires distributed to 326 undergraduate Accounting students at Universitas Brawijaya, with analysis conducted using SmartPLS 4.0. The results indicate that social influence and self-efficacy have a significant effect, while trust and financial literacy do not. These findings suggest that, in the context of Generation Z, the decision to use e-wallets is more influenced by social environmental pressures and individuals’ confidence in their ability to use technology, rather than rational considerations such as trust or financial literacy. Practically, these results can serve as a reference for providers and regulators to encourage e-wallet adoption through social-based strategies, ease of use, and the strengthening of digital literacy.